The Influence of Financial Literacy, Development of Fintech and Payment Gateway on Financial Management Behavior for Faculty Economic and Business Students - Jannah, Amalya Miftahul; Puspita, Erna; Widiawati, Hestin Sri (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research aim : The research was conducted to examine the effect of financial literacy, development of fintech and payment gateways on financial management behavior of students at the Faculty of Economics and Business, Nusantara University PGRI Kediri. Design/Method/Approach : The approach in this study used Associative Quantitative and data collection was obtained by distributing questionnaires through by Google form. The population of this study were 1,887 students from the Faculty of Economics and Business at Nusantara PGRI Kediri University. The sample in this study was calculated based on the slovin formula to obtain a score of 331 students. The technique used was purposive sampling with the criteria being FEB students at Nusantara PGRI Kediri University who used Fintech services. as well as Payment Gateways. Research Finding : Based on the research conducted, it was found that the financial literacy variable (X1) has a positive and significant influence on student financial management behavior (Y). The fintech development variable (X2) has a positive and significant influence on student financial management behavior (Y). The Payment Gateway variable (X3) has a positive and significant influence on student financial management behavior (Y). Theoretical contribution/Originality : - Practitionel/Policy implication : - Research limitation : -